2021
DOI: 10.1613/jair.1.12261
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Democracy: An Algorithmic Perspective

Abstract: We study liquid democracy, a collective decision making paradigm that allows voters to transitively delegate their votes, through an algorithmic lens. In our model, there are two alternatives, one correct and one incorrect, and we are interested in the probability that the majority opinion is correct. Our main question is whether there exist delegation mechanisms that are guaranteed to outperform direct voting, in the sense of being always at least as likely, and sometimes more likely, to make a correct decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 12 publications
5
55
0
1
Order By: Relevance
“…Less informed voters by delegating their votes to more informed agents, enhance the electoral impact of more informed voters (which is desirable), but also remove valuable pieces of information from the aggregation procedure (which is undesirable). This observation is, arguably, of independent interest, since the literature has paid special attention to this trade-off of delegation and tried to assess its sign under alternative behavioral assumptions (see, Kahng et al, 2018). Our work demonstrates rational individuals who choose behaviors endogenously to maximise their individual welfare, can gain from being allowed to delegate votes, despite the partially adverse consequences of vote concentration.…”
Section: Auxiliary Gamementioning
confidence: 74%
See 3 more Smart Citations
“…Less informed voters by delegating their votes to more informed agents, enhance the electoral impact of more informed voters (which is desirable), but also remove valuable pieces of information from the aggregation procedure (which is undesirable). This observation is, arguably, of independent interest, since the literature has paid special attention to this trade-off of delegation and tried to assess its sign under alternative behavioral assumptions (see, Kahng et al, 2018). Our work demonstrates rational individuals who choose behaviors endogenously to maximise their individual welfare, can gain from being allowed to delegate votes, despite the partially adverse consequences of vote concentration.…”
Section: Auxiliary Gamementioning
confidence: 74%
“…In such a setting delegation introduces an additional dilemma: when less informed -yet, not completely uninformed-voters delegate their votes to more informed ones (even if they know who they are), then the electoral impact of more informed voters increases (which is desirable), but pieces of valuable information are left out of the aggregation process (which is undesirable). Whether the net effect of delegation is positive or negative, depends on the exact behavior employed by the voters (Kahng et al, 2018). We prove that the game with delegation admits an equilibrium that is weakly better compared to all equilibria of the game without delegation, even in the presence of such an additional complication.…”
Section: Liquid Democracymentioning
confidence: 85%
See 2 more Smart Citations
“…On the positive side, Green-Armytage (2015) showed that, in a specific spatial voting setting, transitive delegations decrease an expected loss measuring how well the votes represent the voters. On the other hand, Kahng, Mackenzie, and Procaccia (2018), studied a binary election with a ground truth. In their model, no "local" procedure (i.e., a procedure working locally on the SN to organize delegations) can guarantee that LD is, at the same time, never less accurate and sometimes strictly more accurate than direct voting.…”
Section: Related Workmentioning
confidence: 99%